Role of silymarin in the management of deranged liver function in non-alcoholic steatohepatitis: a case report - Yeong Yeh Lee; Vincent Tee (BioExcel Publishing Ltd, 2023)
Non-alcoholic fatty liver disease is one of the main causes of elevated liver enzymes and chronic liver disease worldwide. It ranges from steatosis to steatohepatitis, leading to cirrhosis and related liver dysfunction. Silymarin is a herbal medicine, mostly used for liver disorders owing to its supposed hepatoprotective action. This report recommends silymarin in a patient with diabetes and grade II non-alcoholic steatohepatitis, confirming significant hepatoprotective effects as shown by the reduction of liver enzyme activities. This article is part of the Current clinical use of silymarin in the treatment of toxic liver diseases: a case series Special Issue: https://www.drugsincontext.com/special_issues/current-clinical-use-of-silymarin-in-the-treatment-of-toxic-liver-diseases-a-case-series